A key system response of diametric space as a paradigm for understanding the phenomenology of anorexia nervosa - Downes, Paul (Frontiers in Psychiatry, 2025)
There is increasing recognition of phenomenological approaches to understanding anorexia nervosa (AN), interrogating lived experiences and voices of those diagnosed with AN. This article builds on phenomenological accounts of AN, taking a step further for a spatial phenomenology, to examine how specific central features of AN experience are structured in diametric spatial terms. Building on growing research on the phenomenology of AN, it is remarkable how consistently the phenomenology of AN clusters around structural features of diametric space, as reactive, compensatory coping mechanisms of splitting, closure, and mirror image inversions. Pervasive features of AN experience and motivation, including control, perfectionism, ambivalence, an anorexic “voice,” the gaze of the other, and self-hate around the body, are all aspects that cluster around the specific spatial system and process of diametric space. Diametric spatial closure from background stimuli offers a spatial concomitant of control. Restriction of food in AN may be part of a wider process of spatial constriction as the operation of a diametric spatial system of experience. This diametric spatial system of experience is in tension with a concentric spatial system, amplifying Ricoeur’s phenomenology of distantiation and Lévi-Strauss’ anthropological insights regarding the interplay between these cross-cultural structures. This conceptual, desk-based review presents a theoretical framework of AN phenomenology as displacement within experiential space, from concentric to diametric space, proposed as a prior system paving the way for bodily tensions in AN, bringing loss of capacity for concentric structured spatial experiences. This treats AN recovery as capacity for restructuring from diametric spatial oppositions to generate connective, relatively open, concentric spaces in life experiences. Developing a spatial interpretative methodology, phenomenological and qualitative AN research sources for application of this spatial analysis were selected based on their direct relevance to key aspects of DSM-5 diagnostic features for AN regarding drive for thinness, body dissatisfaction, and overexercise, as well as for central psychological understandings of AN in terms of control, identity, and perfectionism.